The Influence of Academic Supervision and Principal Leadership on Teachers’ Performance - Muhammad Atik Afwanudin; Dewi Apriani; Tity Kusrina (Journal of Educational Sciences, 2026)
Teachers’ performance is a key factor in achieving effective learning and improving school quality at the junior high school level. Academic supervision and principal leadership are managerial practices that directly influence teachers’ professional performance. This study    aims    to   investigate the effect of academic supervision and principal leadership on teachers’ performance in public junior high schools. A quantitative correlational design was applied, with the population comprising all teachers from public junior high schools in one district. The sample was selected using proportional sampling. Data were collected through validated questionnaires covering academic supervision, principal leadership, and teachers’ performance. Multiple regression analysis was used to examine partial and simultaneous effects among the variables. The results indicate that both academic supervision and principal leadership positively and significantly affect teachers’ performance. When analyzed together, these factors also show a significant combined effect. The findings highlight that effective supervision practices and strong instructional leadership are essential for improving teachers’ work quality. The study concludes that enhancing academic supervision mechanisms and strengthening principal leadership capacity can serve as strategic efforts to improve teachers’ performance in junior high schools.